Comparison of electrical and self-sensing properties of Portland cement and alkali-activated slag mortars. (April 2019) - Rovnaník, P.; Kusák, I.; Bayer, P.; Schmid, P.; Fiala, L.
Abstract: Aluminosilicate-based construction materials are known generally as electrical insulators. The electrical resistivity of cement paste and composites with conductive admixture and the consequent multifunctionality of such materials have been widely studied. Only limited information is provided for other types of aluminosilicate binders. This paper presents a comparison of the electrical properties, especially resistance and capacitance, and consequent self-sensing functionality of Portland cement and alkali-activated slag mortars. The results show that alkali-activated slag shows enhanced conducting properties due to the presence of mobile hydrated sodium ions and metallic iron microparticles. Although the absolute resistivity of alkali-activated slag is quite low, it exhibits sufficient self-sensing properties even without the addition of conductive filler.